Turkish Balkan policy during the golden times of the Cold War - Turan, Sibel (Balcanica Posnaniensia. Acta et studia, 2010)
The study examines Turkey’s Balkan policy between 1950 and 1960 – a decade described as the „golden years” of the Cold War – within the broader framework of East-West tensions and regional realignments. The paper aims to analyze how Turkey, as a newly aligned member of the Western bloc, sought to balance its security interests, regional ambitions, and alliance commitments in a politically fragmented Balkans. The research is based on a historical and analytical approach, using primary diplomatic documents, official correspondence, and scholarly interpretations of Turkish, Balkan, and Western foreign policy sources. The analysis highlights that the post-war division of Europe, codified by the Percentages Agreement and the formation of Cominform, redefined the Balkans as a contested geopolitical space. Turkey’s participation in the formation of the Balkan Pact (1953–1954) with Greece and Yugoslavia represented an attempt to create a regional security structure compatible with NATO objectives and the Western containment strategy. However, subsequent developments – such as Yugoslavia’s non-alignment, the deterioration of Turkish-Greek relations over the Cyprus issue, and Bulgaria’s subordination to Soviet policy – undermined the sustainability of this alliance. The study concludes that Turkey’s Cold War Balkan policy was largely reactive and constrained by superpower rivalry. While Turkey succeeded in strengthening its Western orientation and security guarantees through NATO membership, it simultaneously lost its capacity for autonomous regional diplomacy. Consequently, the „golden years” of the Cold War marked not only a period of intensified Western integration for Turkey but also the gradual erosion of its independent influence in the Balkans.